Research on vector acoustic focusing and shielding technology. (1st October 2016) - Niu, Fang; Hui, Juan; Zhao, Zhi-Shan
Abstract: Vector acoustic focusing and shielding technology was discussed in this paper. Based on time reversal mirror (TRM) theory, the received sound pressure signals which contained radiation noise from the target and interference sources were weighted in the frequency domain. Combination of the output sound pressure signals and received particle velocity signals can form unilateral directivity, so focusing on the target and shielding interference sources can be achieved simultaneously. Shielding weight vector was also calculated when multiple interference sources existed in detection area. In terms of acoustic shielding, interference signal in a selected area was suppressed, so the detection performance to the targets outside the area could be improved. Better than scalar hydrophone array, vector array can distinguish between left and right, and further more, the output "beam" of the array has a narrower main lobe and larger radio of main lobe to side lobe. The simulation indicated that one or multiple interference sources were all suppressed under vector acoustic shielding technology so that detection performance was improved. Highlights: ● Vector acoustic focusing and shielding technology was provided. ● Time reversal mirror (TRM) theory is used in acoustic shielding technology, obtaining good performance. ● Multiple interference sources was successfully shielded under vector acoustic shielding technology.